Gojek VS Grab: Which One Is Better in Creating Customer Satisfaction and Loyalty? - Berto Mulia Wibawa; Grisna Anggadwita; Rachma Rizqina Mardhotillah; Syarief Nur Husin; Alyaa Zalfaa Komara Putri; Siska Lusia Putri (Jurnal Bisnis dan Keuangan, 2022)
Online ride-hailing is now becoming a popular option for customers to travel worldwide, including for consumers in Indonesia. However, the Covid-19 pandemic caused many force majeure problems for companies serving online ride-hailing services. These situations lead to numerous customer dissatisfaction, low switching cost, and disloyalty for customers to use online ride-hailing services. In particular, this study aims to investigate the comparison of customer satisfaction and loyalty level between Gojek and Grab. This study used the online-survey method with a total sample of 569 usable online responses. The data analysis was carried out by calculating the importance-performance analysis, customer satisfaction index, and customer loyalty index. Our findings illustrate that the competition between two companies is very tight and competitive. Based on service satisfaction, Gojek is slightly better than Grab. Nevertheless, in terms of loyalty, the level of loyalty of Grab consumers is more loyal than Gojek consumers. Hence, instead of competing head to head, it would be more effective for Gojek and Grab to have diverse service strategies to provide more varied benefits to society.